2018
DOI: 10.1161/circresaha.117.312052
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Activated FOXO Transcription Factors in the Heart Prolongs Survival in a Mouse Model of Laminopathies

Abstract: FOXO TFs are activated and contribute to the pathogenesis of cardiac phenotype in laminopathies. Suppression of the FOXO TFs in cardiac myocytes partially rescues the phenotype and prolongs survival. The findings identify FOXO TFs as potential therapeutic targets for cardiac phenotype in laminopathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
89
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(92 citation statements)
references
References 65 publications
2
89
1
Order By: Relevance
“…We observed a similar disease progression from 1 week to 1 month. But unlike the former study, which showed a significant decrease in mouse weight in 2-week-old Lmna −/− mice 15 , we did not identify a significant difference in growth between wild type (WT) and Lmna −/− mice at 1 week and 2 weeks of age ( Fig. 1a).…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…We observed a similar disease progression from 1 week to 1 month. But unlike the former study, which showed a significant decrease in mouse weight in 2-week-old Lmna −/− mice 15 , we did not identify a significant difference in growth between wild type (WT) and Lmna −/− mice at 1 week and 2 weeks of age ( Fig. 1a).…”
Section: Resultscontrasting
confidence: 99%
“…Meanwhile, Lmna −/− mice showed down-regulation in key genes in DNA damage response/repair pathways as well as up-regulation in genes involved in the oxidative stress response, acute phase response, cell survival/growth, cardiac hypertrophy, glycolysis, and triglyceride hydrolysis. We identified the up-regulation of FOXO3 (listed in Table 1 apoptosis pathway), which was also found in a previous study in 2-week Lmna −/− mice by Marian et al 15 . However, instead of activation of the pathway in 2-week Lmna D300N mice shown by Marian et al 16 , we identified overall down-regulation of DNA damage response pathway (z score = −1.265).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations